Chronic heat stress increases insulin-like growth factor-1(IGF-1) but does not affect IGF-binding proteins in growing pigs. (October 2018) - Xin, Hairui; Zhang, Xiaojun; Sun, Dengsheng; Zhang, Chuang; Hao, Yue; Gu, Xianhong
Abstract: The insulin-like activity of insulin-like growth factor-1 (IGF-1) is heavily blunted by IGF binding proteins (IGFBPs, including IGFBP-1 and IGFBP-3). The effects of heat stress (HS) on the IGF-1 and IGFBPs in growing pigs are still not clear. This study aimed to investigate the alterations of IGF-1 and IGFBPs under chronic HS in growing pigs. Twenty-seven growing large white barrows with similar body weight were collected from nine litters and were assigned into three treatments. The litter effect is balanced in all treatments. Treatments were: 1) thermal-neutral (TN) group (23 °C), 2) chronic HS group (33 °C), and 3) pair-fed in TN condition (PFTN). The experiment lasted for 21 days. Compared with TN controls, decreased FI, lower average body weight gain, higher rectal temperature and increased respiration rates were observed in HS pigs. On D7, increased plasma insulin concentration and insulin:glucose ratio were observed in HS pigs compared to TN controls. A overall elevation of plasma IGF-1:IGFBP-3 ratio was detected in HS pigs compared with PFTN and TN counterparts. Besides, hepatic IGF-1 gene expression of HS pigs was 50% higher than TN counterparts. PFTN pigs, however, had no differences in plasma IGF-1:IGFBP-3 ratio and hepatic IGF-1 gene expression, compared with TN pigs. PFTN pigs increased plasma IGFBPs concentration and hepatic IGFBPs gene expression, compared with TN controls. However, no differences in plasma IGFBPs concentration and hepatic IGFBPs gene expression were observed between TN and HS group. Liver IRS-1 gene and protein expressions of HS pigs tended to be increased compared with TN controls, while PFTN pigs still kept liver IRS-1 gene and protein expressions in normal level. High temperature (33 °C), independent of feed intake reduction, increased IGF-1 but did not affect IGFBPs levels in growing pigs. Highlights: High temperature, independent feed intake reduction, increases IGF-1:IGFBP-3 ratio. Chronic heat stress upregulated hepatic IRS-1 level but not INSR and IGF-1 receptor levels. Unlike artificial feed restriction, feed intake reduction caused by chronic heat stress has no effects on plasma IGFBPs concentrations of growing pigs.